Exchange-traded funds as an alternative investment option - Afonso, António (2022)
We conduct an analysis of Exchange-traded Funds (ETFs), Index and Equity mutual funds and their respective benchmark during the 2010-2015 period for the Portuguese fund industry. For the period 2010-2017, we test ETFs for price inefficiency (existence of deviations between prices and the Net Asset Value) and persistence. We find that the studied ETF does not always outperform index funds in replicating the variations of the PSI 20 index, despite exhibiting better tracking ability when facing downside deviations of the benchmark and a better capacity of smoothing tracking deviations. Regarding ETFs price efficiency and its persistence, the study reveals that the examined ETF is priced at a low average discount with evidence of deviations persistence of at least two days. The investment schemes with the highest ability to track the PSI 20 Index were PSI20 (ETF), BBVA PPA Índice PSI20, and the equity mutual fund BPI Portugal.